Priprava spletne oglaševalske akcije na iskalniku Bing - Vukasović, Tina; Söke, Henrik (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
The purpose of this paper was to study and present the background for search engine marketing, and on the basis of my findings, to run an actual advertising campaign on the Bing search engine. The empirical part was written using the inductive and deductive research methods, together with quantitative analysis, and my own findings and opinions. Among the most important findings of this research is the necessity of preparing well for the advertising campaign, the significance of writing effective advertising texts, using high converting landing pages, and the importance of analysis of obtained data. The presented study is useful for anyone who’s already using search engine marketing, and for all those, who are interested in starting with search engine marketing. There isn’t much research about Bing Ads in Slovenia yet so this is a great starting point for all futures Bing Ads users. The present content of the article is a continuation of the first part of the article published in the Journal of Innovative Business and Management (Vukasović and Söke, 2016).